Analysis of Risk Factors for Stunting at Semanding Public Health Center, Tuban, Indonesia - Valentino Christianto; Adji Prayitno; Sylvi Irawati; April Nuraini (LPPM Universitas Harapan Bangsa, 2024)
Stunting is a health problem in all developing countries. Stunting causes low intellectual capacity in children, lowers competitiveness, and reduces the quality of human resources in the future. The purpose of this study was to determine the factors causing stunting that can be used as a measure for stunting prevention. A descriptive analysis was conducted using an observational method with a case-control design at the Semanding Community Health Center, Tuban Regency. Sampling was carried out using a total sampling technique with 130 respondents, divided into two groups: mothers with stunted toddlers (65 respondents) and mothers with non-stunted toddlers (65 respondents) from October to December 2023. Bivariate and multivariate data analyses were performed. Significant differences were found in the median maternal age at delivery (p=0.044), child's age when starting complementary foods in addition to breastfeeding (p=0.019), and timing of breastfeeding initiation after birth (p=0.025). The relationship between child characteristics that statistically significantly influenced the incidence of stunting was early initiation of breastfeeding (p=0.027). Early initiation of breastfeeding tended to influence the incidence of stunting